(3KdL GdaDGO aj CMGOjK dHS GdShGOs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3bGd GdTjN GdSjhWi gPG LRA dWja SejJg KdL GdaDGO aj dHS GdShGO Cf GdfHj Udi Gddg Ydjg hSde ONd ecI jhe GdaJM hYdjg YeGeI ShOGA s
(3BNQgG (B:s
(3hcPdc ENJGQ GdfHj Udi Gddg Ydjg hSde dHS YeGeI ShOGA jhe aJM ecg Je HMeO Gddg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B523s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(1027 (3c(B) s
Keywords: (3GdMOjK h GdeUWdMs